Sabertooth mountain - Vornholt, John. (New York : Random House, 1996)
The peaceful world of Dinotopia, an island inhabited by intelligent dinosaurs and shipwrecked humans, is threatened when the sabertooth tigers who live in the Forbidden Mountains are cut off from their normal food supply by an avalanche.
"Bullseye books."
"Based on Dinotopia by James Gurney, published in 1992 by Turner Pub., Inc., Atlanta"--T.p. verso.
4.2
5-8
Keywords: Dinosaurs -- Fiction; Saber-toothed tigers -- Fiction; Islands -- Fiction; Fantasy; Dinosaurs -- Fiction; Saber-toothed tigers -- Fiction; Islands -- Fiction; Fantasy fiction; Fantasy fiction